Home Smart Home : How we want to live - Herwig, Oliver (Birkhäuser, 2022)
Welcome to the hybrid home, in which the bathroom has become a temple of wellness, the living room an online couch, and the kitchen a lounge. Everything appears tidy and chic, perfect for social media. In the Instagram Age, even micro-apartments are mutating into semi-public places. The German journalist Oliver Herwig has been studying the transformation of living spaces and dream interiors for years. In this book, he portrays a society in the throes of digital transformation. The lines between work, leisure and rest have been blurred, as our homes become temporary, multipurpose work, fun and multimedia spaces; the office has invaded the home, and the world of smart shopping is always just a word away thanks to Alexa. Nothing quite fits anymore, yet everything must have its place. Welcome to the hybrid home. Easy reading about the difficult transitions in our living spaces Smart and analytical, the book reveals the hidden desires that shape how we live Designed and illustrated by Studio für Gestaltung, Cologne Available in German and English